2020
DOI: 10.1016/j.ekir.2019.10.007
|View full text |Cite|
|
Sign up to set email alerts
|

An Open-Label Pilot Study of Adrenocorticotrophic Hormone in the Treatment of IgA Nephropathy at High Risk of Progression

Abstract: Introduction: IgA nephropathy (IgAN) is the most common glomerulonephritis with high risk of progression to end-stage renal disease in patients with proteinuria >1 g/24 hours. There are no known effective treatments in patients with IgAN. Methods: We conducted a prospective open-label pilot study in patients with IgAN using adrenocorticotrophic hormone (ACTH) (Acthar Gel, Mallinckrodt Pharmaceuticals, Bedminster, NJ) at a dosage of 80 units subcutaneously twice weekly for a total of 6 months and followed patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Nevertheless, both studies found RCI to have a substantially lower prednisone‐equivalent dose than clinically relevant doses of synthetic ACTH 1‐24 depot. Despite having a low estimated daily prednisone‐equivalent dose, RCI has previously demonstrated clinical efficacy in patients with inflammatory conditions that have shown a poor clinical response to corticosteroids 8–18 . This further supports a therapeutic effect of RCI that is independent of cortisol production and suggests that RCI may be an efficacious alternative for patients who have become resistant to the effects of corticosteroids or are unable to tolerate their side effects.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Nevertheless, both studies found RCI to have a substantially lower prednisone‐equivalent dose than clinically relevant doses of synthetic ACTH 1‐24 depot. Despite having a low estimated daily prednisone‐equivalent dose, RCI has previously demonstrated clinical efficacy in patients with inflammatory conditions that have shown a poor clinical response to corticosteroids 8–18 . This further supports a therapeutic effect of RCI that is independent of cortisol production and suggests that RCI may be an efficacious alternative for patients who have become resistant to the effects of corticosteroids or are unable to tolerate their side effects.…”
Section: Discussionmentioning
confidence: 78%
“…Repository corticotropin injection (RCI; Acthar Gel) has demonstrated therapeutic benefit for persistent inflammatory disorders and other conditions that have exhibited an inadequate response to corticosteroids and standard‐of‐care treatments 8–18 . RCI is approved by the US Food and Drug Administration for the treatment of infantile spasms and various allergic, autoimmune, inflammatory, and rheumatic diseases.…”
mentioning
confidence: 99%
“…Administration of a 6-month course of ACTH gel in patients with IgAN at high risk of progression (proteinuria > 1 g per 24 h despite documented ACEI/ARB therapy and adequate blood pressure control for >3 months, 24-h creatinine clearance >30 mL/min/1.73 m 2 ) was prospectively investigated in an open-label pilot study (NCT 02282930). A significant decline in 24-h urinary protein (2.6 to 1.3 g; p = 0.007) with no significant changes in eGFR (65.5 to 61.1 mL/min, p = 0.1) was detected at 12-month follow-up in patients with IgAN treated with 6 months of ACTH [58].…”
Section: High Risk Patients With Iganmentioning
confidence: 88%
“…[13][14][15][16] A recent pilot study using adrenocorticotropic hormone (ACTH) treatment in a patient with a high risk of IgA progression showed a significant reduction of proteinuria with stable estimated glomerular filtration rate (eGFR) at 12 months post-therapy with no significant adverse events. 17 The mechanism for anti-proteinuric effect of ACTH therapy is not fully understood, but in addition to corticosteroid release the effect may be related to the activation of the melanocortin-1 receptor, which has a podocyte protective effect. 18…”
Section: Discussionmentioning
confidence: 99%